Analisis Faktor Ekonomi Yang Mempengaruhi Tingkat Kemiskinan Pada Saat Krisis Di Kota Surabaya - Martha Hendrati, Ignatia; Aprilianti, Hera (Jurnal Riset Ekonomi dan Bisnis, 2009)
The purpose of this study is to determine how much economic factors affecting the level of poverty in the city of Surabaya. In an effort to improve the living standards of poor communities especially in the city of Surabaya. This study uses secondary data during the 12 years since the years 1996-2007 using multiple linear regression analysis calculations to determine the relationship and influence simultaneously and partially from Population Growth variables (X1), Investment (X2), Education Subsidy (X3), and Level Education (X4) as the independent variable on the variables in Surabaya City Poverty Rate (Y) as the dependent variable. Results obtained from testing the hypothesis that the variables X1, X2, X3, and X4 significant effect Poverty Level variable, this is indicated by the test F test = 5.613> Ftable = 4.12. The analysis tool used is multiple linear regression by using data for 12 yearsKeywords: Poverty, Poor Communities, Education Subsidy, City Poverty Rate